Intra-abdominal Pressure Monitoring in Open Abdomen Management with Dynamic Abdominal Closure - Sarer, A. Ebru (Indian J Surg, 2016)
The importance of elevated intra-abdominal pressure (IAP) and abdominal compartment syndrome (ACS) have been recognized in critical care for its potential damaging effects. But, quantification of IAP values may be useful as a clinical tool for determining efficacy of coughing and straining for functional recovery of OA patients. We would like to evaluate IAP generated in an OA patient and the effect of negative pressure therapy (NPT) and dynamic abdominal closure systems (ABRA) on the IAP values at rest and during coughing and straining and compare those with IAP measurements of closed abdomen after standard open elective colorectal surgery (non-OA). Eight OA and eight non-OA patients were included in this study. OA patient with NPT and ABRA (OA + NA), OA patient without NPT and ABRA completely unbraced (OA-NA) (NA stands for NPT and ABRA), and non-OA patients underwent IAP measurements at rest, during coughing, and during straining via transurethral catheter. There was no difference in the mean of IAP measurement at rest in OA-NA (6.1 mmHg), OA + NA (6.5 mmHg), and non-OA (6.0 mmHg) patients. During coughing, IAP of OA-NA, OA + NA, and non-OA patients were 11.5, 19.1, and 22.0 mmHg and during straining, IAP of OA-NA, OA + NA, and non-OA patients were 11.5, 17.5, and 23.5 mmHg, respectively. Application of NPT in conjunction with ABRA did not increase IAP at rest but provided significant IAP increase in OA + NA patients, when compared to OA-NA patients during coughing and straining. NPT in conjunction with ABRA offers the advantage of increase of IAP during coughing and straining.